PROJECT-BASED LEARNING IN TEACHING WRITING RECOUNT TEXT - Muhammad Farich; Ahmad Syafi’I; Haris Dibdyaningsih (Journal of English Language Teaching and Islamic Integration, 2022)
Writing recount text, therefore, is very important for students to master since it develops students’ writing skill in delivering chronological information. This skill later, will be needed in higher education or in university. In writing recount text, students will deliver information in the sequence of: the introduction, the sequences of information and the conclusion students will work in team and support each other in the project. Students will think more complex rather than writing a simple text in the learning. Thus, project based learning is considered as a learning strategy for teaching writing..